Evaluation of the use of heterologous fibrin biopolymer and hydroxyapatite/tricalcium phosphate synthetic ceramic, associated or not with photobiomodulation therapy, in the repair of bone defects - Reis, Carlos Henrique Bertoni (2023)
Extensive bone loss resulting from fractures or tumor resection poses a challenge for tissue bioengineering areas, in the search for morphological and functional recomposition in a shorter period. The joint use of low-level laser (currently called photobiomodulation therapy - PBM) and bioproducts provides new horizons for tissue repair with a greater chance of success, such as, for example, biocomplexes consisting of fibrin sealant and particulate biomaterials. Objectives: In article 1, the systematic review aimed to evaluate the relationship between PBM and the use of fibrin compounds, referring to the results of previous studies published in PubMed/MEDLINE, Scopus and Web of Science databases and, in article 2, to evaluate the grafting of hydroxyapatite/tricalcium phosphate (BCP) ceramic biomaterial (B) together with the heterologous fibrin biopolymer (FB) and with photobiomodulation (PBM) in the repair process of bone defects. Materials and methods: In article 1, the descriptors fibrin AND low-level laser therapy and fibrin AND photobiomodulation were used, without restriction on publication time. In article 2, fifty-six rats were randomly divided into four groups of seven animals each: the biomaterial group (G1/B), the biomaterial plus FB group (G2/BFB); the biomaterial plus PBM group (G3/B + PBM), and the biomaterial plus FB plus PBM group (G4/BFB + PBM). After anesthesia, a critical defect was performed in the center of the rats parietal bones, then filled and treated according to their respective groups. The rats were euthanized at 14 and 42 postoperative days. Results: In article 1, the bibliographic search found 44 articles in PubMed/MEDLINE, of which 26 were excluded due to duplicity or being outside the eligibility criteria. We also found 40 articles in Web of Science and selected 1 article, 152 articles in Scopus and no article selected, totaling 19 articles for qualitative analysis. The fibrin type most used in combination with PBM was fibrin sealant, mainly heterologous, followed by PRF or L-PRF. In PBM, the gallium-aluminum-arsenide (GaAlAs) laser prevailed, with a wavelength of 830 nm, followed by 810 nm. Among the preclinical studies, the most researched association of fibrin and PBM was the use of fibrin sealants in bone or nerve injuries; in clinical studies, the association of PBM with medication-related treatments osteonecrosis of the jaw (MRONJ). In article 2, in the comparison between the groups, in the two experimental periods (14 and 42 days), in relation to the percentage of formation of new bone tissue, a significant difference was found between all groups (G1/B (5.42 ± 1.12; 21.49 ± 4.74), G2/BFB (5.00 ± 0.94; 21.77 ± 2.83), G3/B + PBM (12.65 ± 1.78; 29.29 ± 2.93), and G4/BFB + PBM (12.65 ± 2.32; 31.38 ± 2.89)). Conclusion: The literature consulted on PBM, associated with fibrin compounds, scores positive results in several areas of tissue bioengineering, mainly in the recovery of extensive bone loss and peripheral nerve injuries. The reproducibility of research in this area presents problems, due to the numerous protocols that are used and not always fully described in scientific articles. The interaction of the biocomplex composed of Hydroxyapatite/Tricalcium Phosphate Ceramic and Fibrin Biopolymer was potentially effective in the reconstruction of critical bone defects in the calvaria of rats, because the combined use generated perspectives of faster regeneration than when biomaterials and biopharmaceuticals are used separately.